A preparation process for anti-pollution acrylic resin glass fiber casing

By using amino alkane modified acrylic resin, amino alkane modified polysiloxane and stearic acid modified nanotitanium dioxide, a high hydrophobicity and high temperature resistance coating is formed, which solves the problems of easy damage to the glass fiber sleeve and insufficient coating performance, and achieves superhydrophobic, anti-pollution and high temperature resistance effects.

CN118988693BActive Publication Date: 2025-03-25DONGGUAN HAOYIDA NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411344070.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-03-25
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing fiberglass sleeves are prone to breakage during use, and the coating lacks superhydrophobic, pollution-resistant and high temperature resistance.

Method used

Amino alkane modified acrylic resin, amino alkane modified polysiloxane and stearic acid modified nanotitanium dioxide are used as the main components of the glass fiber casing surface coating. Through hydrogen silicon addition reaction and polymerization reaction, a coating with high hydrophobicity and high temperature resistance is formed.

Benefits of technology

The superhydrophobic, pollution-resistant and high-temperature resistance of the surface of the glass fiber sleeve is achieved, and the structural stability and service life of the sleeve are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005060475780000032
    Figure BDA0005060475780000032
  • Figure BDA0005060475780000033
    Figure BDA0005060475780000033
  • Figure BDA0005060475780000101
    Figure BDA0005060475780000101
Patent Text Reader

Abstract

The present invention relates to the technical field of glass fiber casing, and discloses a preparation technology of a pollution-resistant acrylic resin glass fiber casing, aminoalkane modified acrylic resin, aminoalkane modified polysiloxane, stearic acid modified nano titanium dioxide are added to a flask, epoxy resin is added, and the solution is coated on the glass fiber casing after stirring, and heat curing is performed to obtain pollution-resistant acrylic resin glass fiber casing. The water contact angle of the glass fiber casing surface coating of the present invention reaches 150.9-153.5 °, showing super-hydrophobic characteristics, can be pollution-resistant and self-cleaning advantages. Simultaneously modified acrylic resin and modified polysiloxane contain amino groups, and when high temperature curing, curing crosslinking reaction can occur with epoxy resin, forming a tight chemical crosslinking network in the coating system, improving the high temperature resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fiber sleeves, in particular to a preparation process of a pollution-resistant acrylic resin glass fiber sleeve. Background Art

[0002] Glass fiber insulation sleeve is a sleeve material obtained by reinforcing and weaving glass fiber. It has the advantages of good insulation and can be used to place wires, electronic components, etc. in the sleeve. It is widely used in power equipment and other fields. However, during the use of glass fiber sleeve, due to its low strength and high brittleness, when it comes into contact and friction with external objects, it will cause the glass fiber sleeve to be damaged, seriously affecting the safety of the internal parts of the sleeve.

[0003] Applying polymer coating on glass fiber insulation sleeve can improve the impact resistance and friction resistance of the sleeve, and at the same time, the surface sleeve can be polluted. Acrylic resin has good mechanical properties, high transparency, excellent weather resistance, and is widely used in glass fiber sleeves, electronic and electrical equipment, etc. Patent CN111945437B discloses a highly flame-retardant and corrosion-resistant glass fiber sleeve, which uses modified water-based acrylic resin, water-based alkyd resin, water-based epoxy resin, nano titanium dioxide, organic modified montmorillonite, nano silicon dioxide hollow microspheres, rare earth oxides, composite flame retardants, etc. as the coating layer of the glass fiber sleeve, which can give the glass fiber sleeve high flame retardancy, corrosion resistance, high temperature resistance and other properties. However, the raw materials of the patent coating are complicated, and the coating layer does not have a super hydrophobic self-cleaning and anti-pollution system. Summary of the invention

[0004] The technical problem solved by the invention is to provide an acrylic resin glass fiber sleeve which is super hydrophobic, anti-pollution and high temperature resistant.

[0005] Technical solution: A preparation process of anti-pollution acrylic resin glass fiber casing:

[0006] (1) Toluene, aminoalkane acrylate monomer, and isopropanol solution of chloroplatinic acid are added to a flask, nitrogen is introduced, and hydrogen-containing silicone oil is added. After the reaction, the mixture is distilled under reduced pressure, washed with methanol, and dried to obtain aminoalkane-modified polysiloxane.

[0007] (2) Deionized water, methyl (meth)acrylate, aminoalkane acrylate monomer, and emulsifier are added to a flask, an initiator is added dropwise, nitrogen is introduced, a preliminary reaction is carried out, methyl (meth)acrylate, aminoalkane acrylate monomer, and initiator are further added, a polymerization reaction is carried out, and the material is cooled and discharged to obtain an aminoalkane-modified acrylic resin.

[0008] The structural formula of aminoalkane acrylate monomer is: n is any integer between 11 and 17;

[0009] (3) Adding aminoalkane-modified acrylic resin, aminoalkane-modified polysiloxane, and stearic acid-modified nano-titanium dioxide into a flask, stirring and dispersing them at high speed, then adding epoxy resin, coating the solution on a glass fiber sleeve after stirring, and performing thermal curing to obtain an anti-pollution acrylic resin glass fiber sleeve.

[0010] Preferably, the ratio of aminoalkane acrylate monomer to hydrogen-containing silicone oil in (1) is (0.12-0.18 g):1 g.

[0011] Preferably, the reaction temperature in (1) is 90-100° C. and the reaction time is 12-18 h.

[0012] Preferably, in (2), the emulsifier is OP-10 and sodium dodecyl sulfate; and the initiator is potassium persulfate or ammonium persulfate.

[0013] Preferably, the ratio of methyl (meth)acrylate to aminoalkane acrylate monomer in (2) is 1 mol:(0.08-0.2) mol.

[0014] Preferably, in (2), the pre-reaction temperature is 60-75°C, and the reaction time is 60-90 min; the polymerization reaction temperature is 60-75°C, and the reaction time is 3-4 h.

[0015] Preferably, in (3), the ratio of aminoalkane-modified acrylic resin, aminoalkane-modified polysiloxane, stearic acid-modified nano-titanium dioxide, and epoxy resin is 1 g: (0.05-0.2) g: (0.15-0.4) g: (0.02-0.1) g.

[0016] Preferably, the heat curing in (3) is first carried out at 60-80°C for 4-6 hours and then at 100-120°C for 2-4 hours.

[0017] Preferably, the preparation process of aminoalkane acrylate monomer is:

[0018] S1. Add dichloromethane, BOC-DL-serine (CAS No. 3850-40-6) in a ratio of 1 mol:(0.9-1.1) mol:(0.9-1.1) mol, alkyl acyl chloride compound, and triethylamine to a flask, react for 10-20 min in an ice-water bath, then stir and react for 12-18 h at room temperature, distill under reduced pressure, wash with petroleum ether, and recrystallize from chloroform to obtain intermediate A. The structural formula of the alkyl acyl chloride compound is n is any integer between 11 and 17. The preparation reaction formula is as follows:

[0019]

[0020] S2. Add toluene, intermediate A in a ratio of 1 mol:(1-1.1) mol:(0.06-0.08) mol, hydroxyethyl acrylate, and p-toluenesulfonic acid into a flask, react at 80-90°C for 10-15h, distill under reduced pressure, and recrystallize from chloroform. Then add the product to trifluoroacetic acid and dichloromethane, react at room temperature for 3-5h, add 15% ammonia water to adjust the pH of the solution to 8-9, add deionized water, shake, extract and separate, distill the organic phase under reduced pressure, and recrystallize from chloroform to obtain an aminoalkane acrylate monomer. The preparation reaction formula is as follows:

[0021]

[0022] Technical effect of the present invention: The present invention utilizes novel aminoalkane acrylate monomers to undergo silylation reaction with hydrogen-containing silicone oil and polymerization reaction with monomers such as methyl acrylate, and the obtained aminoalkane-modified acrylic resin and aminoalkane-modified polysiloxane contain a large amount of amino groups and hydrophobic alkyl long chains.

[0023] The present invention utilizes aminoalkane modified acrylic resin, aminoalkane modified polysiloxane, and stearic acid modified nano titanium dioxide as the main component of the glass fiber casing surface coating, polysiloxane itself has very strong hydrophobicity, and introduces alkyl long chain, further improves the hydrophobicity of polysiloxane, and the molecular chain of acrylic resin and the surface alkyl long chain of nano titanium dioxide also contain alkyl long chain, now the hydrophobicity of coating is enhanced, and it is conducive to improving the water contact angle. And after the alkyl long chain is introduced into the surface of nano titanium dioxide, there is good interface compatibility between the aminoalkane modified acrylic resin and aminoalkane modified polysiloxane containing alkyl long chain, and alkyl chain crosslinking and hydrophobic association occur, the dispersibility of nano titanium dioxide in acrylic resin system is enhanced, micro-nano level protrusion and rough structure can be well formed, so that the water contact angle of coating reaches 150.9-153.5°, showing super hydrophobic property, and having the advantages of anti-pollution and self-cleaning.

[0024] The aminoalkane-modified acrylic resin, aminoalkane-modified polysiloxane and stearic acid-modified nano titanium dioxide of the present invention all contain long alkyl chains, and the three have good compatibility, the system is uniformly dispersed and stable, and the phenomenon of phase separation is not likely to occur, which can improve the structural stability of the cured coating. In addition, the long alkyl chains of the three undergo chain entanglement crosslinking and hydrophobic association, which is beneficial to improving the high temperature resistance of the coating. At the same time, the modified acrylic resin and the modified polysiloxane contain amino groups, which can undergo curing and crosslinking reactions with epoxy resin during high temperature curing, forming a compact chemical crosslinking network in the coating system, and further improving the high temperature resistance of the coating. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0026] 50 mg of nano titanium dioxide (average particle size 30 nm) was added to 30 mL of ethanol and ultrasonically dispersed. Then 4 g of stearic acid was added and stirred for dispersion. The mixture was heated to 80°C and refluxed for 2 h. The mixture was centrifuged and the precipitate was washed with ethanol and dried to obtain stearic acid-modified nano titanium dioxide.

[0027] Example 1

[0028] (1) Add 8 mL of dichloromethane, 4 mmol of BOC-DL-serine, and 3.6 mmol of dodecanoyl chloride to the flask. 4 mmol triethylamine, react in an ice-water bath for 10 min, then stir and react at room temperature for 18 h, distill under reduced pressure, wash with petroleum ether, and recrystallize from chloroform to obtain intermediate A.

[0029] (2) Add 25 mL of toluene, 5 mmol of intermediate A, 5 mmol of hydroxyethyl acrylate, and 0.4 mmol of p-toluenesulfonic acid into a flask, react at 80° C. for 10 h, distill under reduced pressure, and recrystallize from chloroform. Then add the product to 20 mL of trifluoroacetic acid and 30 mL of dichloromethane, react at room temperature for 5 h, add 15% by mass ammonia water to adjust the pH of the solution to 8, add deionized water, shake, extract and separate, distill the organic phase under reduced pressure, and recrystallize from chloroform to obtain an aminoalkane acrylate monomer.

[0030] (3) Add 15 mL of toluene, 0.9 g of aminoalkane acrylate monomer, and 50 uL of isopropanol solution containing 1 mg of chloroplatinic acid into a flask, introduce nitrogen, add 5 g of hydrogenated silicone oil (brand TSF484), react at 100° C. for 12 h, distill under reduced pressure, wash with methanol, and dry to obtain aminoalkane-modified polysiloxane.

[0031] (4) Add 10 mL of deionized water, 25 mmol of methyl acrylate, 2 mmol of aminoalkane acrylate monomer, 0.06 g of OP-10, and 0.12 g of sodium dodecyl sulfate into a flask, dropwise add 8 mg of initiator potassium persulfate, introduce nitrogen, conduct a pre-reaction at 60° C. for 90 min, then add 75 mmol of methyl acrylate, 6 mmol of aminoalkane acrylate monomer, and 36 mg of initiator potassium persulfate, conduct a polymerization reaction for 4 h, cool the material, and obtain an aminoalkane-modified acrylic resin.

[0032] (5) Add 20 g of aminoalkane-modified acrylic resin, 1 g of aminoalkane-modified polysiloxane, and 8 g of stearic acid-modified nano-titanium dioxide into a flask, stir and disperse at high speed, then add 0.4 g of epoxy resin, and after stirring, apply the solution on the glass fiber sheathing, first heat cure at 70°C for 4 h, and then heat cure at 120°C for 2 h to obtain an anti-pollution acrylic resin glass fiber sheathing.

[0033] Example 2

[0034] (1) Add 12 mL of dichloromethane, 4 mmol of BOC-DL-serine, and 4.4 mmol of palmitoyl chloride to the flask. 4.4 mmol triethylamine, react in an ice-water bath for 10 min, then stir and react at room temperature for 12 h, distill under reduced pressure, wash with petroleum ether, and recrystallize from chloroform to obtain intermediate A.

[0035] (2) Add 30 mL of toluene, 5 mmol of intermediate A, 5.5 mmol of hydroxyethyl acrylate, and 0.36 mmol of p-toluenesulfonic acid into a flask, react at 80° C. for 15 h, distill under reduced pressure, and recrystallize from chloroform. Then add the product to 20 mL of trifluoroacetic acid and 30 mL of dichloromethane, react at room temperature for 4 h, add 15% by mass ammonia water to adjust the pH of the solution to 9, add deionized water, shake, extract and separate, distill the organic phase under reduced pressure, and recrystallize from chloroform to obtain an aminoalkane acrylate monomer.

[0036] (3) Add 10 mL of toluene, 0.8 g of aminoalkane acrylate monomer, and 50 uL of isopropanol solution containing 1 mg of chloroplatinic acid into a flask, introduce nitrogen, add 5 g of hydrogenated silicone oil, react at 90° C. for 18 h, distill under reduced pressure, wash with methanol, and dry to obtain aminoalkane-modified polysiloxane.

[0037] (4) Add 15 mL of deionized water, 25 mmol of methyl methacrylate, 3 mmol of aminoalkane acrylate monomer, 0.07 g of OP-10, and 0.14 g of sodium dodecyl sulfonate into a flask, dropwise add 10 mg of initiator ammonium persulfate, introduce nitrogen, conduct a pre-reaction at 75° C. for 60 min, then add 75 mmol of methyl methacrylate, 11 mmol of aminoalkane acrylate monomer, and 40 mg of initiator ammonium persulfate, conduct a polymerization reaction for 3 h, cool the material, and obtain an aminoalkane-modified acrylic resin.

[0038] (5) Add 20 g of aminoalkane-modified acrylic resin, 2.5 g of aminoalkane-modified polysiloxane, and 6 g of stearic acid-modified nano-titanium dioxide into a flask, stir and disperse at high speed, then add 1 g of epoxy resin, and after stirring, apply the solution on the glass fiber sheathing, first heat cure at 80°C for 4 h, and then heat cure at 100°C for 4 h to obtain an anti-pollution acrylic resin glass fiber sheathing.

[0039] Example 3

[0040] (1) Add 12 mL of dichloromethane, 4 mmol of BOC-DL-serine, and 3.6 mmol of stearyl chloride to the flask. 3.6 mmol triethylamine, react in an ice-water bath for 20 min, then stir and react at room temperature for 15 h, distill under reduced pressure, wash with petroleum ether, and recrystallize from chloroform to obtain intermediate A.

[0041] (2) Add 25 mL of toluene, 5 mmol of intermediate A, 5.5 mmol of hydroxyethyl acrylate, and 0.3 mmol of p-toluenesulfonic acid into a flask, react at 90° C. for 10 h, distill under reduced pressure, and recrystallize from chloroform. Then add the product to 25 mL of trifluoroacetic acid and 30 mL of dichloromethane, react at room temperature for 3 h, add 15% by mass ammonia water to adjust the pH of the solution to 8, add deionized water, shake, extract and separate, distill the organic phase under reduced pressure, and recrystallize from chloroform to obtain an aminoalkane acrylate monomer.

[0042] (3) Add 10 mL of toluene, 0.6 g of aminoalkane acrylate monomer, and 50 uL of isopropanol solution containing 0.8 mg of chloroplatinic acid into a flask, introduce nitrogen, add 5 g of hydrogenated silicone oil, react at 90° C. for 12 h, distill under reduced pressure, wash with methanol, and dry to obtain aminoalkane-modified polysiloxane.

[0043] (4) Add 15 mL of deionized water, 25 mmol of methyl methacrylate, 5 mmol of aminoalkane acrylate monomer, 0.07 g of OP-10, and 0.14 g of sodium dodecyl sulfonate into a flask, dropwise add 10 mg of initiator potassium persulfate, introduce nitrogen, conduct a pre-reaction at 70° C. for 90 min, then add 75 mmol of methyl methacrylate, 15 mmol of aminoalkane acrylate monomer, and 42 mg of initiator potassium persulfate, conduct a polymerization reaction for 3 h, cool and discharge the material to obtain an aminoalkane-modified acrylic resin.

[0044] (5) Add 20 g of aminoalkane-modified acrylic resin, 4 g of aminoalkane-modified polysiloxane, and 3 g of stearic acid-modified nano-titanium dioxide into a flask, stir and disperse at high speed, then add 2 g of epoxy resin, and after stirring, coat the solution on the glass fiber sheathing, first heat cure at 60°C for 6 h, and then heat cure at 100°C for 4 h to obtain an anti-pollution acrylic resin glass fiber sheathing.

[0045] Comparative Example 1

[0046] (1) Prepare aminoalkane-modified polysiloxane in the same manner as in Example 1.

[0047] (2) Prepare aminoalkane-modified acrylic resin in the same manner as in Example 1.

[0048] (3) Add 20 g of aminoalkane-modified acrylic resin, 1 g of aminoalkane-modified polysiloxane, and 8 g of nano-titanium dioxide into a flask, stir and disperse at high speed, then add 0.4 g of epoxy resin, and after stirring, apply the solution on the glass fiber sheathing, first heat cure at 70°C for 4 h, and then heat cure at 120°C for 2 h to obtain an anti-pollution acrylic resin glass fiber sheathing.

[0049] Comparative Example 2

[0050] (1) The aminoalkane-modified acrylic resin was prepared in the same manner as in Example 1.

[0051] (2) Add 20 g of aminoalkane-modified acrylic resin, 1 g of hydrogen-containing silicone oil, and 8 g of stearic acid-modified nano-titanium dioxide into a flask, stir and disperse at high speed, then add 0.4 g of epoxy resin, and after stirring, apply the solution on the glass fiber sheathing, first heat cure at 70°C for 4 h, and then heat cure at 120°C for 2 h to obtain an anti-pollution acrylic resin glass fiber sheathing.

[0052] Comparative Example 3

[0053] (1) Prepare aminoalkane-modified polysiloxane in the same manner as in Example 1.

[0054] (2) Add 10 mL of deionized water, 25 mmol of methyl acrylate, 0.06 g of OP-10, and 0.12 g of sodium dodecyl sulfate into a flask, dropwise add 8 mg of initiator potassium persulfate, introduce nitrogen, conduct a pre-reaction at 60° C. for 90 min, then add 75 mmol of methyl acrylate and 36 mg of initiator potassium persulfate, conduct a polymerization reaction for 4 h, cool and discharge the material to obtain an acrylic resin.

[0055] (3) Add 20 g of acrylic resin, 1 g of aminoalkane-modified polysiloxane, and 8 g of stearic acid-modified nano-titanium dioxide into a flask, stir and disperse at high speed, then add 0.4 g of epoxy resin, and after stirring, apply the solution on the glass fiber sheathing, first heat cure at 70°C for 4 h, and then heat cure at 120°C for 2 h to obtain an anti-pollution acrylic resin glass fiber sheathing.

[0056] Comparative Example 4

[0057] (1) Prepare aminoalkane-modified polysiloxane in the same manner as in Example 1.

[0058] (2) Prepare aminoalkane-modified acrylic resin in the same manner as in Example 1.

[0059] (3) Add 20 g of aminoalkane-modified acrylic resin, 1 g of aminoalkane-modified polysiloxane, and 8 g of stearic acid-modified nano-titanium dioxide into a flask, disperse them by high-speed stirring, and apply the solution on the glass fiber sheath. First, heat cure it at 70°C for 4 h, and then heat cure it at 120°C for 2 h to obtain an anti-pollution acrylic resin glass fiber sheath.

[0060] The water contact angle on the surface of anti-pollution acrylic resin glass fiber casing was tested according to the method of GB / T 30693-2014.

[0061] Table 1 Water contact angle test on glass fiber casing surface

[0062] Water contact angle (°) Example 1 153.5 Example 2 150.9 Example 3 151.3 Comparative Example 1 142.1 Comparative Example 2 151.2 Comparative Example 3 147.4 Comparative Example 4 153.7

[0063] As can be seen from the test results in the above table, aminoalkane modified acrylic resin, aminoalkane modified polysiloxane, stearic acid modified nano titanium dioxide are utilized as the main component of glass fiber casing surface coating in embodiments 1 to 3, polysiloxane itself has very strong hydrophobicity, and introduced alkyl long chain, further improved polysiloxane hydrophobicity, the molecular chain of acrylic resin simultaneously, the surface alkyl long chain of nano titanium dioxide also contains alkyl long chain, now enhanced the hydrophobicity of coating, conducive to improving water contact angle.And after the surface of nano titanium dioxide introduces alkyl long chain, with the aminoalkane modified acrylic resin containing alkyl long chain, aminoalkane modified polysiloxane three have good interface compatibility, and alkyl chain crosslinking and hydrophobic association occur, enhanced the dispersibility of nano titanium dioxide in acrylic resin system, can well form micro-nano level protrusion and rough structure, thereby make the water contact angle of coating reach 150.9-153.5 °, show super hydrophobicity, can be anti-pollution and self-cleaning advantage.

[0064] Compared with Example 1, the difference of Comparative Example 1 is that unmodified nano titanium dioxide is added, which does not contain hydrophobic alkyl long chains, and has poor compatibility with aminoalkane-modified acrylic resin and aminoalkane-modified polysiloxane. The alkyl chain cross-linking and hydrophobic association make it difficult to disperse in the acrylic resin coating system, and it is easy to agglomerate, and it is impossible to form good micro-nano-scale protrusions and rough structures. The water contact angle of the coating surface is only 144.1°.

[0065] The hydrogenated silicone oil added in Comparative Example 2 does not contain long alkyl chains, has lower hydrophobicity than aminoalkane-modified polysiloxane, and has poor compatibility with stearic acid-modified nano-titanium dioxide and aminoalkane-modified acrylic resin, resulting in a lower water contact angle on the coating surface than in Example 1.

[0066] The acrylic resin added in Comparative Example 3 does not contain a hydrophobic alkyl long chain, and has poor compatibility with stearic acid-modified nano-titanium dioxide and aminoalkane-modified polysiloxane, resulting in a lower water contact angle on the coating surface than that in Example 1.

[0067] The difference between Comparative Example 4 and Example 1 is that without adding epoxy resin, the coating still has a very high water contact angle, showing excellent superhydrophobic self-cleaning and anti-pollution properties.

[0068] The anti-pollution acrylic resin fiberglass casing was placed at different temperatures for 240 hours and the appearance of the casing was observed to see if there was yellowing or cracking.

[0069] Table 2 Heat resistance test of anti-pollution acrylic resin glass fiber casing surface

[0070]

[0071]

[0072] As can be seen from the test results in the above table, aminoalkane modified acrylic resin, aminoalkane modified polysiloxane, and stearic acid modified nano titanium dioxide are used as the main components of the glass fiber casing surface coating in embodiments 1 to 3, and the coating does not turn yellow or crack at high temperatures, and shows good high temperature resistance and weather resistance. This is because modified acrylic resin, modified polysiloxane, and modified nano titanium dioxide all contain alkyl long chains, and the three have good compatibility, and the system is uniformly dispersed and stable, and the phenomenon of phase separation is not good, which can improve the structural stability of the cured coating. And the chain entanglement crosslinking and hydrophobic association of the three alkyl long chains are conducive to improving the high temperature resistance of the coating. Modified acrylic resin and modified polysiloxane contain amino groups at the same time, and when high temperature curing, curing crosslinking reaction can occur with epoxy resin, forming a tight chemical crosslinking network in the coating system, further improving the high temperature resistance of the coating.

[0073] In Comparative Example 1, unmodified nano-titanium dioxide is added, which has poor compatibility with aminoalkane-modified acrylic resin and aminoalkane-modified polysiloxane, is not dispersed in the coating, and is prone to agglomeration, resulting in phase separation in the system and cracking of the coating at high temperatures.

[0074] The hydrogenated silicone oil added in Comparative Example 2 does not contain long alkyl chains and amino groups, and the acrylic resin added in Comparative Example 3 does not contain long alkyl chains and amino groups. They cannot form a good hydrophobic association, nor can they form a chemically cured cross-linked network with the epoxy resin, resulting in poor high temperature resistance of the coating, and yellowing and cracking are prone to occur at high temperatures.

[0075] In Comparative Example 4, no epoxy resin is added, and a chemical curing cross-linking network cannot be formed with the aminoalkane-modified polysiloxane and the aminoalkane-modified acrylic resin, resulting in poor high temperature resistance of the coating, and yellowing and cracking easily occur at high temperatures.

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A process for preparing a pollution-resistant acrylic resin glass fiber sleeve, characterized in that: The preparation process is: (1) adding toluene, aminoalkane acrylate monomer, and isopropanol solution of chloroplatinic acid into a flask, introducing nitrogen, adding hydrogen-containing silicone oil, performing reduced pressure distillation after the reaction, washing with methanol, and drying to obtain aminoalkane-modified polysiloxane; (2) adding deionized water, methyl (meth)acrylate, aminoalkane acrylate monomer, and emulsifier into a flask, dropping an initiator, introducing nitrogen, conducting a preliminary reaction, further adding methyl (meth)acrylate, aminoalkane acrylate monomer, and initiator, conducting a polymerization reaction, cooling and discharging the material to obtain an aminoalkane-modified acrylic resin; The structural formula of the aminoalkane acrylate monomer is: n is any integer between 11 and 17; (3) adding aminoalkane-modified acrylic resin, aminoalkane-modified polysiloxane, and stearic acid-modified nano-titanium dioxide into a flask, stirring and dispersing them at high speed, and then adding epoxy resin, coating the solution on the glass fiber sleeve after stirring, and performing thermal curing to obtain an anti-pollution acrylic resin glass fiber sleeve; The ratio of aminoalkane acrylate monomer to hydrogen-containing silicone oil in (1) is (0.12-0.18 g): 1 g; The reaction temperature in (1) is 90-100° C. and the reaction time is 12-18 h; The ratio of methyl (meth)acrylate to aminoalkane acrylate monomer in (2) is 1 mol:(0.08-0.2) mol; In said (2), the pre-reaction temperature is 60-75°C, and the reaction time is 60-90min; the polymerization reaction temperature is 60-75°C, and the reaction time is 3-4h; The ratio of aminoalkane-modified acrylic resin, aminoalkane-modified polysiloxane, stearic acid-modified nano-titanium dioxide and epoxy resin in (3) is 1g: (0.05-0.2)g: (0.15-0.4)g: (0.02-0.1)g.

2. The process for preparing the pollution-resistant acrylic resin glass fiber sleeve according to claim 1, characterized in that: The emulsifier in (2) is OP-10 and sodium dodecyl sulfate; the initiator is potassium persulfate or ammonium persulfate.

3. The process for preparing the pollution-resistant acrylic resin glass fiber sleeve according to claim 1, characterized in that: In the step (3), the thermal curing is first carried out at 60-80°C for 4-6 hours and then at 100-120°C for 2-4 hours.

4. The process for preparing the pollution-resistant acrylic resin glass fiber sleeve according to claim 1, characterized in that: The preparation process of the aminoalkane acrylate monomer is as follows: S1. Add dichloromethane, BOC-DL-serine, alkyl acyl chloride and triethylamine in a ratio of 1 mol:(0.9-1.1) mol:(0.9-1.1) mol to a flask, react for 10-20 min in an ice-water bath, then stir at room temperature for 12-18 h, distill under reduced pressure, wash with petroleum ether, and recrystallize from chloroform to obtain intermediate A; S2. Add toluene, intermediate A in a ratio of 1 mol: (1-1.1) mol: (0.06-0.08) mol, hydroxyethyl acrylate and p-toluenesulfonic acid into a flask, react at 80-90°C for 10-15h, distill under reduced pressure, and recrystallize from chloroform. Then add the product to trifluoroacetic acid and dichloromethane, react at room temperature for 3-5h, add ammonia water to adjust the pH of the solution to 8-9, add deionized water, shake, extract and separate, distill the organic phase under reduced pressure, and recrystallize from chloroform to obtain an aminoalkane acrylate monomer.

5. The process for preparing the pollution-resistant acrylic resin glass fiber sleeve according to claim 4, characterized in that: The structural formula of the alkyl acyl chloride compound is that n is any integer between 11-17.

Citation Information

Patent Citations

  • A high flame-retardant and corrosion-resistant glass fiber sleeve

    CN111945437B

  • Preparation method of super-hydrophobic coating with phase change function

    CN103666159A

  • Preparation method of anti-ultraviolet silicon dioxide-acrylic resin composite coating

    CN115838567A